Tropical and Subtropical Fruit Propagation - Jeff Wasielewski; Carlos F. Balerdi (EDIS, 2019)
Propagation is an important technique used by tropical and subtropical fruit growers worldwide, allowing plants to be grown cheaply and efficiently. While sexual propagation (by seed) results in plants that are not genetically the same as the mother plant, asexual propagation (cuttings, division, air-layers, and grafting) creates offspring that are clones of the mother plant. Cloning fruit trees is important because it allows different cultivars to be preserved over time. This new 7-page publication of the UF/IFAS Horticultural Sciences Department explains both sexual and asexual propagation techniques, why they are used, and what type of propagation is best for which species of tropical fruit. Written by Jeff Wasielewski and Carlos Balerdi. https://edis.ifas.ufl.edu/hs1349